Trade unions, equal pay and the law in the UK. (May 2014) - Conley, Hazel
Trade unions in the UK have traditionally followed a voluntarist strategy that has preferred collective bargaining and avoided the use of the law wherever possible. The exception to this has been in relation to the pursuit of equal pay between women and men. This article examines this apparent contradiction by examining the ways in which British trade unions have used the equality legislation in the past to secure equal pay through the courts. The article further considers recent legislative changes that, by adopting a reflexive approach, appeared to open up ways for equality bargaining to take place. Unfortunately the conclusion is not a positive one as political conservatism in relation to equality and judicial animosity towards trade unions have secured the status quo, ironically forcing trade unions to continue to use adversarial legal methods to pursue equal pay.